2011
DOI: 10.4103/0972-5229.83017
|View full text |Cite
|
Sign up to set email alerts
|

Serum lactate levels as the predictor of outcome in pediatric septic shock

Abstract: Background and Aims:An association of high lactate levels with mortality has been found in adult patients with septic shock. However, there is controversial literature regarding the same in children. The aim of this study was to find the correlation of serum lactate levels in pediatric septic shock with survival.Settings and Design:This was a prospective observational study at PICU of a tertiary care center of North India.Materials and Methods:A total of 30 children admitted to PICU with diagnosis of septic sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
55
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 41 publications
5
55
1
4
Order By: Relevance
“…Jat, et al [1] also reported similar mortality rate (50%) in their cohort of children with septic shock. The vasoactive-inotrope score (VIS) is a simple, clinical tool, easy to use, and based on bedside hemodynamic parameter to monitor cardiovascular support in critically ill child with septic shock.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Jat, et al [1] also reported similar mortality rate (50%) in their cohort of children with septic shock. The vasoactive-inotrope score (VIS) is a simple, clinical tool, easy to use, and based on bedside hemodynamic parameter to monitor cardiovascular support in critically ill child with septic shock.…”
Section: Discussionsupporting
confidence: 65%
“…Multiple factors have been identified as a predictor for poor outcome of septic shock among children [1,5]. Kutko, et al [5] in their retrospective review of children with septic shock found that the high mortality rate was associated with the presence of multiorgan dysfunction syndrome.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Более высо-кую прогностическую точку демонстрирует работа, в которой уровни лактата выше 10 ммоль/л и насы-щение кислорода в венозной крови (SvO 2 , %) меньше 50 % связаны с развитием полиорганной недостаточ-ности [18]. В исследовательских работах показано наличие корреляции лактата с оценками по шкалам тяжести состояния и исхода [1, 4,6,[11][12][13][14][15]. Таким образом, место и значимость маркера лактата как в диагностическом, так и в прогностическом аспек-тах окончательно не определено.…”
unclassified